2020
DOI: 10.1242/dmm.044925
|View full text |Cite
|
Sign up to set email alerts
|

The SDHB Arg230His mutation causing familial paraganglioma alters glycolysis in a new Caenorhabditis elegans model

Abstract: The conserved B-subunit of succinate dehydrogenase (SDH) participates in the TCA cycle and mitochondrial electron transport. The Arg230His mutation in SDHB causes heritable pheochromocytoma/paraganglioma (PPGL). In C. elegans, we generated an in vivo PPGL model (SDHB-1 Arg244His; equivalent to human Arg230His) which manifests delayed development, shortened lifespan, attenuated ATP production and reduced mitochondrial number. Although succinate is elevated in both missense and null sdhb-1(gk165) mutants, transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…These Arg244His SDHB mutants demonstrated elevated lactate/pyruvate levels, pointing to a missense-induced, Warburg-like aberrant glycolysis. Authors concluded that mutation in the amino acid sequence of SDHB rewires metabolism, resembling metabolic reprogramming in cancer [ 60 ]. Similar observations have been reported by other scientists who showed strong evidence that some mutations in SDH impair oxidative phosphorylation, which highly contributes to the Warburg metabolism switch observed in cancer cells [ 61 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…These Arg244His SDHB mutants demonstrated elevated lactate/pyruvate levels, pointing to a missense-induced, Warburg-like aberrant glycolysis. Authors concluded that mutation in the amino acid sequence of SDHB rewires metabolism, resembling metabolic reprogramming in cancer [ 60 ]. Similar observations have been reported by other scientists who showed strong evidence that some mutations in SDH impair oxidative phosphorylation, which highly contributes to the Warburg metabolism switch observed in cancer cells [ 61 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to hyperoxia. Succinate accumulation, damaged oxygen consumption [ 83 , 84 ] Cell-specific sdhb-1(RNAi) C. elegans Cell-specific sdhb-1(RNAi) Also used DMOG to suppress SDH. Crosses with HIF mutants [ 85 ] Copy of human mutation in SDHB C. elegans Arg244His point mutant (corresponding to Arg230His in human SDHB ) Succinate accumulation, damaged oxygen consumption, increased pyruvate and lactate levels, increased LDH activity.…”
Section: Model Systemsmentioning
confidence: 99%
“…Crosses with HIF mutants [ 85 ] Copy of human mutation in SDHB C. elegans Arg244His point mutant (corresponding to Arg230His in human SDHB ) Succinate accumulation, damaged oxygen consumption, increased pyruvate and lactate levels, increased LDH activity. Sterile adults [ 84 ] mev-1 C. elegans G71E in SDHC mev-1 was discovered in a worm screen for oxygen sensitivity. G71E mutants display oxygen hypersensitivity, decreased lifespan and brood size phenotypes.…”
Section: Model Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“… ABSTRACT First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Éva Saskői is first author on ‘ The SDHB Arg230His mutation causing familial paraganglioma alters glycolysis in a new Caenorhabditis elegans model ’, published in DMM. Éva is a PhD student in the lab of Krisztina Takács-Vellai at Eötvös Lorand University, Budapest, Hungary, investigating the developmental functions of tumor suppressor homologs in Caenorhabditis elegans .…”
mentioning
confidence: 99%